Bardet‐Biedl syndrome: Antenatal presentation of forty‐five fetuses with biallelic pathogenic variants in known Bardet‐Biedl syndrome genes. Issue 3 (18th February 2019) - Mary, Laura; Chennen, Kirsley; Stoetzel, Corinne; Antin, Manuela; Leuvrey, Anne; Nourisson, Elsa; Alanio‐Detton, Elisabeth; Antal, Maria C.; Attié‐Bitach, Tania; Bouvagnet, Patrice; Bouvier, Raymonde; Buenerd, Annie; et al.
Abstract : Bardet‐Biedl syndrome (BBS) is an emblematic ciliopathy associated with retinal dystrophy, obesity, postaxial polydactyly, learning disabilities, hypogonadism and renal dysfunction. Before birth, enlarged/cystic kidneys as well as polydactyly are the hallmark signs of BBS to consider in absence of familial history. However, these findings are not specific to BBS, raising the problem of differential diagnoses and prognosis. Molecular diagnosis during pregnancies remains a timely challenge for this heterogeneous disease (22 known genes). We report here the largest cohort of BBS fetuses to better characterize the antenatal presentation. Prenatal ultrasound (US) and/or autopsy data from 74 fetuses with putative BBS diagnosis were collected out of which molecular diagnosis was established in 51 cases, mainly in BBS genes (45 cases) following the classical gene distribution, but also in other ciliopathy genes (6 cases). Based on this, an updated diagnostic decision tree is proposed. No genotype/phenotype correlation could be established but postaxial polydactyly (82%) and renal cysts (78%) were the most prevalent symptoms. However, autopsy revealed polydactyly that was missed by prenatal US in 55% of the cases. Polydactyly must be carefully looked for in pregnancies with apparently isolated renal anomalies in fetuses. Abstract : A, Fraction of BBS genes involved in our cohort of 45 fetuses with a Bardet‐Biedl syndrome. B, BBS decision tree for the identification of disease‐causing variations in BBS patients.